The association of maternal HIV status during pregnancy on longitudinal neuro-immune regulation, and neurodevelopment in HIV-exposed uninfected children - Sevenoaks, Tatum (Department of Psychiatry and Mental Health, 2021)
Introduction: It has long been established that the Human Immunodeficiency Virus (HIV) and its effects, such as its impact on the immune system and then the numerous consequences on other biological systems including the central nervous system (CNS), have had a significant effect worldwide. This is particularly relevant in South Africa, where the prevalence of adults living with HIV remains high. However, with the improved access to antiretroviral therapy (ART), more children are now being born uninfected with HIV while still being exposed to the virus in utero. Exposure to HIV in utero may still negatively affect the developing brain of these children. However, the biological mechanisms involved in the neurodevelopmental outcomes in HIV-exposed uninfected (HEU) children are still largely unknown. Evidence from clinical studies showed that HEU children have an altered immune regulation compared to their unexposed counterparts, and this is hypothesised to play a role in neurodevelopmental outcomes in HEU children. The aim of this study was to evaluate the longitudinal relationship between the inflammatory environment of pregnant mothers living with HIV on ART and their children and the association of the inflammatory environment with neurodevelopmental outcomes in HEU children. Methods: This study was performed in a sub-sample of the Drakenstein Child Health Study (DCHS), a South African birth cohort of 1137 mother-infant pairs. This sub-study included mothers at ≈26 weeks gestation (n=267), their infants at 6-10 weeks (n=222) and children at 24-28 months (n=267). Maternal HIV status was determined at ≈26 weeks gestation. This sub-study included n=190 HIV negative mother-infant pairs and n=77 HIV positive mother-infant pairs. Serum inflammatory markers (Granulocyte-macrophage colony-stimulating factor (GM CSF), Interferon-γ (IFN-γ), Interleukin IL-1β, IL-2, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12p70, IL-13, tumour necrosis factor-α (TNF-α), neutrophil gelatinase-associated lipocalin (NGAL/Lcn2) and metalloproteinase-9 (MMP-9)) were analyzed in all study participants with a multiplex bead array and ELISA. The Bayley Scales of Infant and Toddler Development (Bayley-III) were used to assess the neurodevelopmental domains: cognitive, motor, language, social-emotional behaviour and adaptive behaviour at 24-28 months of age. Results: Mothers living with HIV on ART had significantly lower levels of the inflammatory markers GM-CSF and MMP9 compared to mothers without HIV. Serum levels of inflammatory markers IFN-γ and IL-1β were significantly lower in HEU infants at 6-10 weeks compared to HIV-unexposed uninfected (HUU) infants. At 24-28 months of age, HEU children also proved to have significantly lower serum levels of the inflammatory markers IFN-γ, IL-1β, IL-2 and IL-4 compared with HUU children. Increased levels of the inflammatory markers; GM-CSF, IFN-γ, IL-10, IL-12p70, IL-1β, IL-2, IL-4, IL-6 and Lcn2 in HEU infants at 6-10 weeks of age was associated with impaired motor neurodevelopment at 24-28 months of age. Conclusion: This is the first study to evaluate the longitudinal associations of immune markers with neurodevelopment in HEU children. The results show that maternal HIV infection was associated with lower levels of inflammatory markers in mothers and their children. Our results further indicate that an altered immune system in HEU infants, specifically at the earliest stages of life, was associated with impaired motor function at 2 years of age. These findings may provide further insights into the involvement of immune regulation, linking maternal HIV status and neurodevelopment in South African HEU children.